Differential regulation of vaginal lipocalins (OBP, MUP) during the estrous cycle of the house mouse - Černá, Martina; Kuntová, Barbora; Talacko, Pavel; Stopková, Romana; Stopka, Pavel (Scientific reports, 2017)
Female house mice produce pheromone-carrying major urinary proteins (MUPs) in a cycling manner, thus reaching the maximum urinary production just before ovulation. This is thought to occur to advertise the time of ovulation via deposited urine marks. This study aimed to characterize the protein content from the house mouse vaginal flushes to detect putative vaginal-advertising molecules for a direct identification of reproductive states. Here we show that the mouse vaginal discharge contains lipocalins including those from the odorant binding (OBP) and major urinary (MUP) protein families. OBPs were highly expressed but only slightly varied throughout the cycle, whilst several MUPs were differentially abundant. MUP20 or 'darcin', was thought to be expressed only by males. However, in females it was significantly up-regulated during estrus similarly as the recently duplicated central/group-B MUPs (sMUP17 and highly expressed sMUP9), which in the mouse urine are male biased. MUPs rise between proestrus and estrus, remain steady throughout metestrus, and are co-expressed with antimicrobial proteins. Thus, we suggest that MUPs and potentially also OBPs are important components of female vaginal advertising of the house mouse.
Keywords: Mice; Vagina; lipokaliny; estrální cyklus; vagina; Female; Estrous Cycle; Lipocalins; Animals; Pheromones; ženské pohlaví; feromony; zvířata; myši